(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: This study aims to analyze the overall satisfaction with work-life balance practices among women teachers in higher secondary schools in Sivagangai using the Neural Network (NN) method. Recognizing the critical role of work-life balance in influencing job satisfaction and overall well-being, this research focuses on identifying key factors that impact the satisfaction levels of women teachers. Data was collected through a structured questionnaire, encompassing various dimensions of work-life balance practices and overall satisfaction. The NN method was employed to develop a predictive model that effectively captures the complex relationships between these variables. The results highlight significant predictors of satisfaction, providing insights into how work-life balance practices can be optimized to enhance the well-being and job satisfaction of women teachers. This study offers valuable recommendations for educational institutions and policymakers to create supportive environments that foster both professional and personal fulfillment for women educators in higher secondary schools.